The period of manifestation of type 1 diabetes mellitus in children and adolescents living on the territory of ZATO (Closed administrative-territorial entity) - Мargarita V Proskurina; Tatiana E Taranushenko; Natalia G Kiseleva (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2022)
Type 1 diabetes mellitus (T1DM) in children and adolescents remains one of the urgent problems of pediatric endocrinology. There is a constant increase in disease rates, both worldwide and Russia. The occurrence of pathology in childhood leads to a decrease in the quality of life of patients and their parents, the early development of chronic complications and disability, which makes type 1 diabetes a social problem in  society. Despite numerous scientific works devoted to the study of the factors of manifestation of the disease, the causes of the occurrence are still unclear and ambiguous.  The purpose of the study: is to identify and study possible clinical and laboratory features of the onset of type 1 diabetes in children and adolescents permanently residing in the territory of closed administrative-territorial entities (ZATO).  Materials and methods: a continuous cohort retrospective study of children with type 1 DM was conducted for the period from 2009-2019, permanently residing in the ZATO territory to  obtain data related to the period of manifestation of the disease. The study group included 55 children from 0 - 18 years of age suffering from type 1 diabetes.  Results: Data on the anamnesis of life and disease, and indicators of clinical and laboratory studies (fasting glycemia, postprandial glycemia, average daily glycemia, average amplitude of glycemia fluctuations and glycated hemoglobin) at the time of disease manifestation are presented. A comparative analysis was carried out with the indicators of the Krasnoyarsk Territory, Russia, the obtained features were described.